Personification in the Islamic archecture from positive and negative views and its results - sarem , wafaa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The research gives a clear image about Personification from the role of jurists and caliphs and what they serve in this field. Personification taboo or not ? and the results of that taboo. From the development of the written, the plants, and the engeering ornamention . thus, come out the muslim artist.they decorated the mosques with many painting. Some of them continued the process of Personification as a result of caliphs promotion. And the Ummayad palacs are an evidence about that. Although it was far from the religious Personification.Bringing the promising artists and led to the development and prosperity at the same time raised the anger and resentment some of the men ofreligion and that the more hotred increased evidence the photograghy, photograghy schools. These schools have left with thousands of images, great graphics. The saying of prohibiting the diagnosis is not with Allah some thing went of. Prohibition say a negative impact in some cases and the same time of the impact.Aparallel positive thus pay the muslim artist to search for new means of.